Quasi-z-source inverter for photovoltaic power gene ration systems - Pravin P. Kalubarme,; Prof. Santhosh Kompelli , (International Journal of Innovations in Engineering Research and Technology, 2021)
The Z-Source Inverter (ZSI) has been reported suitable for residential PV system because of the capability ofvoltage boost and inversion in a single stage. Recently, four new topologies, the quasi-Z-Source Inverters(qZSI), have been derived from the original ZSI. This project analyzes one voltage fed topology of these fourin detail and applies it to PV power generation systems. By usingthe new quasi-Z-Source topology, theinverter draws a constant current from the PV array and is capable of handling a wide input voltage range. Italso features lower component ratings and reduced source stresscompared to the traditional ZSI. A prototypewhich provides three phase 50-Hz, 230Vrms ac has been built in laboratory. It is demonstrated from thetheoretical analysis and MATLAB/SIMULATION results that the proposed qZSI can realize voltage buck orboost and dc-ac inversion in a single stage with high reliabilityand efficiency, which makes it well suited forPV power systems.